Desenhos da escrita - o xamanismo mamãe ursa: transviceração, agenciamento e invenção - Arvelos, Erika de Freitas (2020)
This study is the result of an ethnographic research about Shamanism “Mamãe Ursa”. It was carried out at the places “Centro de Estudos e Práticas de Xamanismo Mamãe Ursa” and at the “Espaço Luanda”, in the city of Uberlândia, Minas Gerais State, Brazil. The manuscript presents the descriptions and translations of my visits to the locations, covering ceremonies, rituals, retreats, dialogues and participant observations. All of these events were held with and about the conductor of shamanic practices. This person is Maria Luisa Galvão, known as Luisa Galvão, the “Mamãe Ursa” or Mama Bear (translated freely). The group of people who is involved in these practices (the organization team, supporters and participants) also were object of observation. The systematization of the elements necessary for the “conclusion” of the research aims was accomplished analyzing these plural relationships. The goals of this study were to describe some expressions of practice, among them, part of Luisa Galvão's life trajectory and the history of the development of Shamanism “Mamãe Ursa”. These topics were included aiming to identify how are organized and articulated the representations of the culture of the Original Peoples. From the identification of the translation process carried out by Luisa Galvão, we came to the interpretation that the convergence between both knowledge is based on the mediation. Both are carried out with and together with non-human things, or rather, with quasi-objects, to use the term of symmetric anthropology, from a composite agency.